The Effect of Commitment Mediation through the Relationship Betwen Confidence and Performance Supply Chain - Moh Mukhsin (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2019)
The purpose of this study is to look for answers to research problems items, namely the effect of trust on supply chain performance through commitment as an intervening variable. This study uses a quantitative method with a questionnaire as a technique of data collection conducted on 70 respondents items, namely Tofu and Tempeh Craftsmen as samples in Banten Province. Data from all three variables was Analyzed using the program Structural Equation Model (SEM)in the Software Smart PLS 2.0. m3 version, The results of this study based on statistical analysis show that the trust has a significant and significant effect on supply chain performance. trust has a positive and significant effect on the commitment and the commitment has a positive and significant effect as an intervening variable on supply chain performance. The results of this study provide very important implications for the role of management to maintain the commitment in the relationship between trust and supply chain performance.